A conceptual paper on the process of understanding the concept of HUBB (LOVE) in the Qur’an - Nur Ad-Diina Shamsudin,; Ashinida Aladdin, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Qur’an is a linguistic miracle that was revealed in the Arabic language to mankind. However, not everyone can fully understand this divine revelation as Arabic is not everyone’s mother tongue. Therefore, to facilitate non-native Arabic speakers to understand the Qur’an, many efforts have been made, including in studying the concepts that are present in the Qur’an, through for example, the Izutsu’s approach (IA) (to investigate the semantic structure of the Qur’an) and the Conceptual Metaphor Theory (CMT) (to investigate the figurative language). While these two approaches have been helpful in assisting individuals to understand the Qur’an, studies that investigate the connection between the two approaches are still lacking. In addition previous research that used either one of the approaches sometimes lack dependency on the exegesis (tafsirs) of the Qur’an; as a result, such studies become less comprehensive. Thus, this conceptual paper proposes how the combination of these two approaches can be used to achieve a better understanding of the concepts stated in the Qur’an The concept of ح ُ ب ّ HUBB (LOVE) is used to achieve this aim.